(untitled) (Fiep Bulletin - online, 2014)
The intestinal parasitic infections are caused by human pathogens, especially in areas with precarious hygiene and health conditions. Its prevalence is higher among children due to their inadequate hygiene habits. This study aims to: identify the parents’ perception of intestinal parasites and self-medication in children enrolled in a pre-school nursery in the city of Serra Grande, PB; to identify the socio-demographic profile of the parents of children in preschool; to investigate the prevalence of self-medication in children with intestinal parasites from the parents’ reports. This is a descriptive study with a quantitative and qualitative approach, developed in the homes of parents or guardians who have children enrolled in that daycare. The sample consisted of 52 parents or guardians, data were collected through a questionnaire and analyzed in the light of relevant literature on the topic. The results show that 90.4% of respondents are female, 50% had completed elementary school. With regard to knowledge about intestinal parasites, 96.2% reported being familiar with them, while 73% said their children have been affected by these diseases. Regarding self-medication, 53.8% said they perform it on their children when they are sick; and of these, 35% and 34%, respectively say that they are self-motivated and self-medicate due to the convenience of knowing the indications of the drugs for parasitic diseases. It is worth noting that respondents have adequate knowledge regarding intestinal parasites; however, to minimize their problems, the vast majority performs self-medication, a habit that can lead to various health consequences of the individual, especially in children, who are more vulnerable, and there is therefore the need to invest in educational measures aimed at raising awareness and reducing this practice.